Development of Gen-M Media Based on Active Learning Approach to Enhance Critical Thinking and Mutual Cooperation Characters in Mathematics Learning for Fifth-Grade Elementary Students - Oky Wulandari; Ida Dwijayanti; Iin Purnamasari (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop Gen-M Media (Dragon Mathematics Educational Game), based on an active learning approach, that is valid, practical, and effective in enhancing students’ critical thinking skills and fostering cooperative character in mathematics learning among fifth-grade elementary school students. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The instruments used included validation sheets, questionnaires, observation sheets, and critical thinking tests. Validation sheets were administered to media experts, material experts, and practitioners to assess the validity and feasibility of the Gen-M media. Questionnaires were distributed to teachers and students to evaluate practicality. Observation sheets were used to assess the development of students’ cooperative character. In addition, pretests and posttests were used to measure critical thinking skills. The data were analyzed using both qualitative and quantitative techniques. The results indicated that: (1) expert and practitioner validation categorized the media as “highly appropriate”; (2) practicality tests yielded scores of 95% from teachers and 91.17% from students, classified as “very practical”; and (3) quantitative analysis confirmed that the Gen-M media significantly improved students’ critical thinking skills by [insert value]% and fostered cooperative character development. In conclusion, the Gen-M media integrated with an active learning approach is a valid, practical, and effective instructional tool that positively influences both the cognitive and social competencies of elementary school students in mathematics education.